2005
DOI: 10.1007/s11095-005-2487-9
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Improvement of Oral Absorption of ME3277 by Prodrug Formation Is Ascribed to the Intestinal Efflux Mediated by Breast Cancer Resistant Protein (BCRP/ABCG2)

Abstract: These results suggest that Bcrp1 plays an important role in the intestinal efflux of ME3277 and, probably, PM-10 and PM-11, metabolites of ME3229, and limits its BA after oral administration of ME3229.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Abcg2 has been shown to account for the efflux of intracellularly formed glucuronide and sulfate conjugates (E3040 glucuronide, E3040 sulfate, and 4-methylumbelliferone sulfate) [1]; the active form of the ester-type prodrug of ME3277 [38] in the small intestine; the biliary excretion of drugs such as nitrofurantoin [51], methotrexate [10], pitavastatin [25], and salfasalazine [86]; and the urinary excretion of methotrexate [10] and E3040 sulfate [56]. As far as the blood-brain barrier is concerned, the importance of BCRP remains controversial.…”
Section: Abcg2 (Bcrp/abcp/mxr)mentioning
confidence: 99%
“…Abcg2 has been shown to account for the efflux of intracellularly formed glucuronide and sulfate conjugates (E3040 glucuronide, E3040 sulfate, and 4-methylumbelliferone sulfate) [1]; the active form of the ester-type prodrug of ME3277 [38] in the small intestine; the biliary excretion of drugs such as nitrofurantoin [51], methotrexate [10], pitavastatin [25], and salfasalazine [86]; and the urinary excretion of methotrexate [10] and E3040 sulfate [56]. As far as the blood-brain barrier is concerned, the importance of BCRP remains controversial.…”
Section: Abcg2 (Bcrp/abcp/mxr)mentioning
confidence: 99%
“…Because BCRP is expressed on the bile canalicular membrane of hepatocytes as well as the brush-border membrane of enterocytes, trophoblast cells in placenta, and the apical membrane of lactiferous ducts in the mammary gland (Maliepaard et al, 2001), BCRP must also be considered as one of the routes for the biliary excretion of organic anions. Current evidence indicates that BCRP contributes to the membrane transport of some substrates, such as intestinal absorption and transfer to breast milk (Jonker et al, 2000(Jonker et al, , 2002Adachi et al, 2004;Mizuno et al, 2004;Kondo et al, 2005;Merino et al, 2005a). Regarding the involvement of BCRP in biliary excretion, some reports have demonstrated that the biliary excretion of 2-amino-1-methyl-6-phenylimidazo(4,5-b)pyridine and nitrofurantoin is almost impaired in Bcrp1(Ϫ/Ϫ) mice (van Herwaarden et al, 2003;Merino et al, 2005a) and that the biliary excretion of topotecan and cimetidine is also mainly regulated by Bcrp, considering the gender difference in the hepatic expression level of Bcrp and the plasma concentration profiles (Merino et al, 2005b).…”
mentioning
confidence: 99%
“…BCRP has been reported to limit the oral availability of topotecan and ME3277, which is produced intracellularly from its ester-type prodrug (Jonker et al, 2002;Kondo et al, 2005). Furthermore, BCRP accepts a variety of sulfate conjugates of xenobiotics as substrates, leading to the hypothesis that Bcrp is involved in the efflux of sulfate conjugates formed intracellularly by SULT.…”
mentioning
confidence: 99%